2008
DOI: 10.1021/ja802210u
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-14 Solid-State NMR Spectroscopy of Aligned Phospholipid Bilayers to Probe Peptide−Lipid Interaction and Oligomerization of Membrane Associated Peptides

Abstract: Characterization of the oligomerization of membrane-associated peptides is important to understand the folding and function of biomolecules like antimicrobial peptides, fusion peptides, amyloid peptides, toxins, and ion channels. However, this has been considered to be very difficult, because the amphipathic properties of the constituents of the cell membrane pose tremendous challenges to most commonly used biophysical techniques. In this study, we present the application of a simple (14)N solid-state NMR spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 76 publications
3
54
2
Order By: Relevance
“…These findings agree well with experimental observations of the immobilization of linear TPA4, as well as support the experimental suggestions that the aggregated ␤-strands of TPA4 cannot diffuse as fast as individual TP-I molecules [15]. These also imply that the oligomerization of those ␤-strands may significantly influence the antimicrobial activity of TP-I, as also observed in the experiments with ␣-helical magainin and their derivatives [41][42][43] and our previous simulations [44]. In this work, our simulations offer insights into the relationship of the peptide structure, aggregation, and mobility in lipid bilayers, but not antimicrobial activity.…”
Section: Interactions Between Peptides and Lipid Bilayerssupporting
confidence: 91%
“…These findings agree well with experimental observations of the immobilization of linear TPA4, as well as support the experimental suggestions that the aggregated ␤-strands of TPA4 cannot diffuse as fast as individual TP-I molecules [15]. These also imply that the oligomerization of those ␤-strands may significantly influence the antimicrobial activity of TP-I, as also observed in the experiments with ␣-helical magainin and their derivatives [41][42][43] and our previous simulations [44]. In this work, our simulations offer insights into the relationship of the peptide structure, aggregation, and mobility in lipid bilayers, but not antimicrobial activity.…”
Section: Interactions Between Peptides and Lipid Bilayerssupporting
confidence: 91%
“…In addition, substantial progress has been in understanding the molecular determinants of AMP activity. For example, recent studies have shown the ability to form oligomeric aggregates in the cell membrane enhances the potency of an AMP (Toke et al, 2004; Tremouilhac et al, 2006; Marquette et al, 2008; Ramamoorthy et al, 2008; Strandberg et al, 2008). Studies have also shown that the presence of d-amino acids (Mangoni et al, 2006) and disulfide bridges (Dhople et al, 2006) can enhance resistance against proteolytic degradation without affecting the antimicrobial activity.…”
Section: Composition Of Membranes Is Key To Amp Selectivitymentioning
confidence: 99%
“…(indicating a change in the membrane surface potential) while the channel-forming peptides did not, opening up the possibility of using this approach to probe the location and orientation of proteins with respect to the membrane [211].…”
mentioning
confidence: 99%